Considerable variation among Iranian dermatologists in the dosing and monitoring of methotrexate for treating psoriasis. (18th October 2013) - Zargari, Omid; Hejazi, Somayeh; Shahidi‐Dadras, Mohamad; Younespour, Shima; Robati, Reza; Firooz, Alireza; Toosi, Parviz; Feldman, Steven R.
Abstract Background Methotrexate (MTX) is a risky medication requiring careful attention to dosing and monitoring. Dosing and monitoring practices are not well characterized. Aims The aim of this study was to assess variation in the dosing and monitoring of methotrexate among Iranian dermatologists. Methods A questionnaire was administered to forty experts in psoriasis concerning the use of MTX. Results Among the 39 responding dermatologists (15 women, 24 men), 54% saw fewer than 10 psoriatic patients per week, 23% 10–20 patients, and 23% more than 20 patients. About half of the dermatologists treat their patients with an initial MTX dose of <7.5 mg/week (range 5–17.5 mg/week), an average dose of <10 mg/week (range 5–25 mg/week), and a maximum dose of <20 mg/week (range 7.5ٲ–50 mg/week) with 71.8% prescribing the medication orally and 28.2% intramuscularly. Subcutaneous injection was preferred by none of the dermatologists as a usual route of administration. Nearly 5% of the dermatologists believe that liver biopsy should be performed prior to treatment with MTX in all patients, and another 5% consider this procedure prior to treatment only in patients with risk factors. About 44 and 33% of the dermatologists do the liver biopsy after 1.0–1.5 g and 3.54 g total cumulative doses, respectively. Conclusion After more than a half century, there are still noticeable controversies on the manner of using MTX in treating psoriasis among Iranian dermatologists. A national guideline may help standardize treatment practices.